Why Don't the Prices of Stocks and Bonds Move Together? - Barsky, Robert B. (American Economic Review, 1989)
The 1970s were associated with very low real interest rates and a large drop in equity values relative to dividends and earnings. This paper explores the possible roles of increased risk and reduced productivity growth in accounting for the behavior of bond and stock prices in a simple general equilibrium model. Both disturbances unambiguously lower the riskless interest rate, but may cause the stock market to respond perversely depending on the degree of aversion to intertemporal substitution and the share of the corporate sector in total wealth.